The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pc.26720
|View full text |Cite
|
Sign up to set email alerts
|

Study on the axial impact of Al‐CFRP thin‐walled tubes with induced design

Abstract: Metal-composite hybrid thin-walled tube has been widely studied due to its excellent lightweight characteristics and crashworthiness. In particular, there are few reports on the research and design of induced metal-composite thinwalled tubes under axial impact. Therefore, the crashworthiness of different induced Al-CFRP tubes was studied in this article by combining experimental and numerical simulation subjected to axial impact. The experimental results showed that the reasonable induced design is helpful to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Lately, hybrid materials were applied as they combine the plastic distortion of metals and the superior specific strength and stiffness of composites. [19][20][21][22][23][24][25][26] Different cross-sectional geometries are commonly implemented in crashworthy elements such as circular, [27][28][29][30] polygon, [31][32][33][34][35] corrugated [36] and multicells. [37][38][39] Energy absorption elements are tested under different loading conditions like axial, [40][41][42] lateral, [43,44] oblique [45,46] and bending.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Lately, hybrid materials were applied as they combine the plastic distortion of metals and the superior specific strength and stiffness of composites. [19][20][21][22][23][24][25][26] Different cross-sectional geometries are commonly implemented in crashworthy elements such as circular, [27][28][29][30] polygon, [31][32][33][34][35] corrugated [36] and multicells. [37][38][39] Energy absorption elements are tested under different loading conditions like axial, [40][41][42] lateral, [43,44] oblique [45,46] and bending.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids have been adapted in energy absorbers as they combine plastic deformation of metallic materials and greater specific stiffness and/or strength of composites 9 , 10 . Many scholars examined the collapse performance of hybrid pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Composites do not exhibit plastic deformation due to the fragility. Composite materials absorb energy by crushing and delamination 7,8 .Hybrids have been adapted in energy absorbers as they combine plastic deformation of metallic materials and greater specific stiffness and/or strength of composites 9,10 . Many scholars examined the collapse performance of hybrid pipes.…”
mentioning
confidence: 99%
“…With ongoing exploration and research into lightweight design and safety, the field of thin-walled structures has rapidly advanced and found widespread application in aerospace. [1][2][3][4] Thin-walled tubes protect passengers and important components by dissipating most impact energy through deformation and destruction during extreme events such as collisions and emergency landings. [5][6][7] Investigations have shown that these energy-absorbing structures are more often used to carry lateral loads.…”
Section: Introductionmentioning
confidence: 99%